2019
DOI: 10.24252/nature.v6i2a1
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage of Kampar’s Rumah Lontiok With Limapuluh Koto’s Rumah Gadang

Abstract: Abstrak_Dalam catatan sejarah, wilayah Kampar pernah menjadi wilayah Rantau (Hilir) dari wilayah Luhak Limapuluh Koto yang merupakan wilayah Darek (Hulu), di mana kedua wilayah ini dihubungkan oleh Sungai Kampar. Wilayah Kampar juga pernah menjadi bagian wilayah Sumatera Tengah, dan pernah dua kali berpisah; pertama oleh pemekaran yang dilakukan oleh Pemerintah Kolonial Belanda dan kedua oleh Presiden Soekarno setelah pemberontakan PRRI-Permesta dikalahkan. Bahkan kedua wilayah ini berbagi sejarah di masa klas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…All of that can be made by the community itself, appropriated, acquired by past eras, or impacted by other communities. The space (genotype) is exceptionally steady and has more grounded linkage, the shape-form (phenotype) is very consistent and has medium linkage, and the style may alter and has weaker linkage (Khamdevi, 2019a(Khamdevi, , 2019b(Khamdevi, , 2020a(Khamdevi, , and 2020b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of that can be made by the community itself, appropriated, acquired by past eras, or impacted by other communities. The space (genotype) is exceptionally steady and has more grounded linkage, the shape-form (phenotype) is very consistent and has medium linkage, and the style may alter and has weaker linkage (Khamdevi, 2019a(Khamdevi, , 2019b(Khamdevi, , 2020a(Khamdevi, , and 2020b.…”
Section: Methodsmentioning
confidence: 99%
“…It is hoped that this research will also describe the relat ionship between the Hulu-Hilir-Pesisir (Upstream-Downstream-Coastal) regions. From the results of previous studies, it was found that there is a linkage of the architectural characteristics of traditional houses in Kampar with houses in Luhak Limopuluh Koto, both of which are connected by the Batang Kampar main river (Khamdevi, 2019b andKhamdevi, 2020a). Likewise, the houses in Kuantan…”
Section: Introductionmentioning
confidence: 99%